2018
DOI: 10.3390/v10100562
|View full text |Cite
|
Sign up to set email alerts
|

Breed Differences in PCV2 Uptake and Disintegration in Porcine Monocytes

Abstract: Porcine circovirus type 2 (PCV2) is associated with various diseases which are designated as PCV2-associated diseases (PCVADs). Their severity varies among breeds. In the diseased pigs, virus is present in monocytes, without replication or full degradation. PCV2 entry and viral outcome in primary porcine monocytes and the role of monocytes in PCV2 genetic susceptibility have not been studied. Here, virus uptake and trafficking were analyzed and compared among purebreds Piétrain, Landrace and Large White and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 64 publications
1
30
0
1
Order By: Relevance
“…2010). Interestingly, previous work from our laboratory demonstrated that monocytic cells, known as scavenger cells and being responsible for cleaning up foreign material in the body, can indeed take up PCV2 virions and disintegrate viral capsids, but have problems with degrading/digesting PCV2 DNA (Wei et al. 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2010). Interestingly, previous work from our laboratory demonstrated that monocytic cells, known as scavenger cells and being responsible for cleaning up foreign material in the body, can indeed take up PCV2 virions and disintegrate viral capsids, but have problems with degrading/digesting PCV2 DNA (Wei et al. 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To amplify the ORF2 gene, a conventional PCR assay was performed using two primer pairs (ORF2-fw: 5′-gcgcacttcttttcgttttcag-3′, ORF2-rev: 5′-gaatgcggccgcttatcacttcgtaatggtttttattattca-3′; pgPCV2-fw: 5′-ggctgtggcctttgktac-3′, pgPCV2-rev: 5′-tgtrgaccacgtaggcctcg-3′) (Lefebvre et al. 2008; Wei et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse and transient binding failure of MAb 3F6 alone was thus mostly due to PCV2 capsid conformational changes. The inhibition of endosome-lysosome acidification increases PCV2 infection in porcine epithelial cells (20), while PCV2 requires an acidic environment in 3D4/31 cells (18) and colocalizes with the lysosomes in primary porcine monocytes (33). The motor-driven transport of vesicles through the cytoplasm might be actin dependent in 3D4/31 cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…PCV2 belongs to the Circovirus genus of the Circoviridae family, conformed by PCV1, PCV2, and PCV3 [15], and has the greatest geographical distribution [16]. PCV2 infects the cells of the immune system, such as the dendritic cells, monocytes, and macrophages [17,18], negatively modulating the regulatory cytokine pattern of the immune response, which causes lymphocyte depletion and immunodeficiency in infected pigs [19][20][21]. This immunodeficiency allows the infection with other concomitant pathogens, which provokes the death of infected animals [22].…”
Section: Introductionmentioning
confidence: 99%